PERANAN CUSTOMER SERVICE DALAM MENINGKATKAN KEPUASAN NASABAH TERHADAP PELAYANAN PERBANKAN DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK UNIT TEHORU CABANG MASOHI MALUKU TENGAH - Dwi Ari Pertiwi (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2023)
This study aims to determine the role of Customer Service in increasing customer satisfaction with banking services of PT Bank Rakyat Indonesia (Persero) Tbk Tehoru Unit Masohi Branch Central Maluku. This research uses qualitative methods of data collection through interviews, observation, direct observation and primary data. Based on the results of the study it can be seen that the efforts of the role of Customer Service in increasing customer satisfaction with banking services have been included in the good category and have been in accordance with what is expected by customers so as to get a positive assessment of customers.